Feeding ecology, density and biomass of the freshwater turtle, Phrynops geoffroanus, inhabiting a polluted urban river in south-eastern Brazil - Souza, Franco Leandro [UNESP]; Abe, Augusto Shinya (My University, 2000)
This study examines the ecology of a population of Geoffroy's side-necked turtle Phrynops geoffroanus inhabiting a polluted urban river in Ribeirão Preto city, São Paulo state, south-eastern Brazil. Adult turtles fed mainly on Chironomidae larvae and pupae (Chironomus cf. plumosus, 100% of occurrence frequency) and domestic waste, but they also consumed terrestrial items (cockroach, snails) and carrion. Juvenile turtles showed more feeding diversity than the adults and exhibited a trend for predation on Chironomidae pupae, but this is not reflected in resource partitioning. The elevated number of turtles (170-230 turtles/ha of river) and biomass (255-345 kg/ha of river) inhabiting this urban river is probably the result of the abundance of sewage and organic waste produced by humans, the absence of predators, and increased availability of nesting areas. Such factors convert this area into an environment highly advantageous for the survival of Geoffroy's side-necked turtle.
Keywords: Biomass; Brazil; Density; Phrynops geoffroanus; Turtle; biomass; feeding ecology; pollution effect; population density; sewage; turtle; Blattaria; Chironomidae; Diptera; Gastropoda; Pleurodira; Testudines; Vertebrata